Electrocatalytic Reduction of Bromothiophenes vs Bromobenzenes on Gold and Silver Electrodes: Enhancement from S specific adsorption and modulation from substituent effects. (20th January 2022) - Grecchi, Sara; Arnaboldi, Serena; Isse, Abdirisak Ahmed; D'Aloi, Chiara; Gennaro, Armando; Mussini, Patrizia R.
Abstract: A voltammetric comparative investigation on the electrochemical activity of substituted bromothiophenes vs bromobenzenes highlights the combined effects of the aromatic or heteroaromatic ring substituents and the sulphur atom on both the intrinsic reactivity (accounted for by experiments on a glassy carbon electrode, assumed to have negligible specific interactions) and the reactivity in the presence of electrocatalytic effects, working on Au or Ag electrodes. The two series of compounds share similarities concerning the dissociative electron transfer mechanism for the reductive cleavage of the C-Br bond, including substituent effects. However, the presence of the sulphur atom in the heteroaromatic series significantly promotes the process both in non-catalytic conditions, on account of electronic effects, and on catalytic electrodes, performing as adsorption auxiliary. The effect is particularly remarkable on Au, partially compensating for the effect of the very negative surface charge, and with significant modulation from the S position with respect to the Br leaving group. The nitrile group might act as an additional adsorption auxiliary besides the S atom. In dibromobithiophene systems Au and Ag catalytic surfaces can also induce a remarkable modification in molecular conformation in order to optimize Br and S interactions with the catalytic surface for both conjugated thiophene rings.